O sentido da República em Esaú e Jacó, de Machado de Assis - Santos, Gilberto de Assis Barbosa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This dissertation has the objective to understand the sense of the representation that Machado de Assis does of the way of the monarchy until republic. The transposition of a historic fate for the fiction is at the penultimate romance that the chronicler published in 1904: Esaú and Jacó. Between others characters, in this narrative the readers will find characters that can impersonate there polarity between monarchists and republicans at the last decades of the empire that had been reeling from the final 60s of the XIX century. This analysis is based, especially, in the way how the events leading the disappearance of the reign Brazilian appears in this enunciation, so as to allow to readers understand the politic game that was in that time and how the partisan dances were maintained by the new regime, opened in the final of the Brazil nineteenth century

Esta dissertação tem como objetivo compreender o sentido da representação que Machado de Assis faz da passagem da Monarquia a República. A transposição de um fato histórico para a ficção se encontra no penúltimo romance que o cronista publicou em 1904: Esaú e Jacó. Entre outras personagens, nesta narrativa os leitores encontrarão personagens que podem personificar a polaridade que existe entre monarquistas e republicanos nas últimas décadas do Império que vinha cambaleando desde o final dos anos 60 do século XIX. A presente análise fundamenta-se, sobretudo, na maneira como os eventos que levaram o desaparecimento do reinado brasileiro aparece nesta enunciação, de forma a possibilitar aos narratários entenderem o jogo político que havia naquele período e como as danças partidárias foram mantidas pelo novo regime, inaugurado no final do Brasil Oitocentista
Keywords: Assis, Machado de 1839-1908 Esaú e Jacó; Ciências sociais; Monarquia; República; Social sciences; Brasil - História